Next Move, Best Move - Cummings, Kimberly (Ascent Audio, 2021)
Kimberly B. Cummings leaves no stone unturned with this thorough, expert guide for professionals seeking to understand how to navigate the world of work. As a former career development adviser in some of the nation's top universities and a diversity + inclusion professional in a Fortune 100 company, Cummings has recognized that people work for the sake of working without understanding how to leverage their unique gifts and position themselves for success. As a result, Next Move, Best Move shares transformational lessons to ensure success and puts the ball back in your court. In Cummings's highly acclaimed book, a specific, effective framework is unveiled to ensure each listener channels and utilizes their highest potential as they regain control and steer professional opportunities in their favor, gaining key information as to: taking stock of their experiences to ensure strategic career moves; discovering how to cultivate and maintain fruitful relationships that support career growth; uncovering how to build a two-year career strategy to move you into future leadership positions; gaining a deeper look into personal and professional branding to ensure alignment with leadership capabilities and career goals; and learning how to use their voice in the workplace to advocate for themselves.
Online resource; Title from title page (viewed July 27, 2021)
Keywords: Audiobooks; Livres audio